1972
DOI: 10.1084/jem.136.4.676
|View full text |Cite
|
Sign up to set email alerts
|

Cell Surface Immunoglobulin

Abstract: Turnover and release of cell surface Ig and secretion of total intracellular Ig has been studied in small lymphocytes from normal mouse spleen. The major findings to emerge are: (a) small lymphocytes secrete 8S IgM and IgG. A small portion of the 8S IgM, but virtually none of the IgG appears to have a cell surface phase. (b) Cell surface IgM is actively turned over with a half-life of 6–8 hr, and turnover can be accounted for by release into the incubation medium. Release is temperature dependent. (c) Released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1973
1973
1988
1988

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 108 publications
(24 citation statements)
references
References 39 publications
(33 reference statements)
2
22
0
Order By: Relevance
“…The present findings extend earlier observations (10) and suggest that cell death is not responsible for these findings. Not only did release occur without evidence of cell death, but release slowed as cells began to die 6-24 h after cultivation.…”
Section: Ssupporting
confidence: 81%
See 3 more Smart Citations
“…The present findings extend earlier observations (10) and suggest that cell death is not responsible for these findings. Not only did release occur without evidence of cell death, but release slowed as cells began to die 6-24 h after cultivation.…”
Section: Ssupporting
confidence: 81%
“…In several experiments precipitates were reduced and alkylated (11), dialyzed (11) and electrophoresed on 5% acrylamide gels in sodium dodecyl sulfate (SDS), or electrophoresed without reduction and alkylation on agarose-2.5% acrylamide gels (10). #, ~, and L chains or 19S IgM, 8S IgM, and 7S IgG served as markers on companion gels.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our earlier studies also reported that IgM was the dominant Ig on the surface of marine splenocytes even when substantial amounts of IgG were being synthesized (4). Three experiments were performed in which thoracic duct cells were enzymatically radioiodinated and the resultant cell lysates acid-and immuno-precipitated.…”
Section: Resultsmentioning
confidence: 99%